Integrating health on air quality assessment — review report on health risks of two major european outdoor air pollutants: PM and NO - Costa, Solange
Quantifying the impact of air pollution on the public's health has become an increasingly critical component in policy discussion. Recent data indicate that more than 70% of the world population lives in cities. Several studies reported that current levels of air pollutants in urban areas are associated with adverse health risks, namely, cardiovascular diseases and lung cancer. IARC recently classified outdoor air pollution and related particulate matter (PM) as carcinogenic to humans. Despite the air quality improvements observed over the last few years, there is still continued widespread exceedance within Europe, particularly regarding PM and nitrogen oxides (NOx). The European Air Quality Directive 2008/50/EC requires Member States to design appropriate air quality plans for zones where air quality does not comply with established limit values. However, in most cases, air quality is only quantified using a combination of monitored and modeled data and no health impact assessment is carried out. An integrated approach combining the effects of several emission abatement measures on air quality, impacts on human health, and associated implementation costs enables an effective cost-benefit analysis and an added value to the decision-making process. Hence, this review describes the basic steps and tools for integrating health into air quality assessment (health indicators, exposure-response functions). In addition, consideration is given to two major outdoor pollutants: PM and NO2. A summary of the health metrics used to assess the health impact of PM and NO2 and recent epidemiologic data are also described.